Cyclin E1 and cyclin E2 in ER+ breast cancer: prospects as biomarkers and therapeutic targets. Issue 5 (May 2020) - Milioli, H H; Alexandrou, S; Lim, E; Caldon, C E
Abstract : Cyclin E1 is one the most promising biomarkers in estrogen receptor positive (ER+) breast cancer for response to the new standard of care drug class, CDK4/6 inhibitors. Because of its strong predictive value, cyclin E1 expression may be used in the future to triage patients into potential responders and non-responders. Importantly, cyclin E1 is highly related to cyclin E2, and both cyclin E1 and cyclin E2 are estrogen target genes that can facilitate anti-estrogen resistance and can be highly expressed in breast cancer. However cyclin E1 and E2 are often expressed in different subsets of patients. This raises questions about whether the expression of cyclin E1 and cyclin E2 have different biological drivers, if high expressing subsets represent different clinical subtypes, and how to effectively develop a biomarker for E-cyclin expression. Finally, several pan-CDK inhibitors that target cyclin E-CDK2 activity have reached Phase II clinical trials. In this review, we outline the data identifying that different cohorts of patients have high expression of cyclins E1 and E2 in ER+ cancer and address the implications for biomarker and therapeutic development.